Comparative study of effectiveness of pap smear versus visual inspection with acetic acid for mass screening of lesions of cervix - Dasari, Mercy Mrudula; Anem, Venkatalakshmi; Gunta, Sirisha; Seeram, Satish Kumar; Atla, Bhagyalakshmi (International Journal of Research in Medical Sciences, 2018)
Background: Cervical cancer is a leading cause of morbidity and mortality among women worldwide and more over in the developing countries, so there is a need to develop screening test with high specificity and sensitivity. Aim of the study was to evaluate the effectiveness of Papanicolaou (PAP) smear versus visual inspection acetic acid (VIA) for screening cervical lesions in patients and to determine and compare their sensitivity and specificity. Methods: The present study is a hospital based prospective study for a period of two years at the department of pathology from August 2014 to July 2016 consisting of 500 patients attending gynaecology outpatient clinic. Papanicolaou (Pap) smear tests and visual inspection acetic acid were employed along with complete clinical history record. The results of VIA were correlated with that of pap smear on the basis of sensitivity, specificity and positive and negative predictive value. Results: Out of 500 cases, most common age group was 21 to 40 years of age consisting of 305 cases - 61%. VIA was positive in 156 cases-31.2%, PAP smear positive for epithelial cell abnormalities were 60 cases-12%. VIA showed higher sensitivity (52.38%) compared to Pap smear (40%) whereas Pap smear showed higher specificity (93.2%) compared to VIA (92.4%). Conclusions: Papanicolaou test is a better screening test for epithelial cell abnormality than VIA. However, in countries with low resource settings where cytology-based screening programs are not available, VIA is a promising alternative.